Copper(I) and gold(I) thiolate precursors to bimetallic nanoparticles. (15th November 2018) - Royappa, A. Timothy; Tran, Chau M.; Papoular, Robert J.; Khan, Mohsan; Marbella, Lauren E.; Millstone, Jill E.; Gembicky, Milan; Chen, Banghao; Shepard, William; Elkaim, Erik
Graphical abstract: Copper(I) and gold(I) thiolate precursors in nanoparticle synthesis, (MSR) n (M = AuI or CuI) were synthesized as solid powders. The gold(I) thiolates were amorphous, with significant aurophilic interactions. The copper(I) thiolates were crystalline, consisting of extended Cu–S sheets with no discernible cuprophilic interactions, separated by layers of hydrogen bonded thiol side chains. Abstract: Copper(I) and gold(I) thiolates were synthesized in quantitative or near-quantitative yield by the direct reaction of aqueous Cu(NO3 )2 or HAuCl4 with aqueous thiols HSCH2 CH2 OH and HSCH2 CH2 OCH2 CH2 OH. The resulting highly insoluble thiolates had spectroscopic and bulk characteristics consistent with the formation of coordination polymers of general formula [M(SR)] n . The gold(I) thiolates were found to be amorphous solids with significant aurophilic interactions. The copper(I) thiolates, however, formed crystalline solids without discernible cuprophilic interactions. Characterization of the solid state structure of these latter thiolates showed that they consisted of covalently linked ca. two-atom thick Cu–S layers separated by layers of hydrogen bonded thiol side chains.